SYSTEMATICITY OF L1 THAI LEARNERS' ENGLISH INTERLANGUAGE OF DEPENDENT PREPOSITIONS - Sumonsriworakun, Piyaboot; Pongpairoj, Nattama (Universitas Pendidikan Indonesia, 2017)
The study investigates systematicity in English interlanguage of dependent prepositions among L1 Thai learners of L2 English. It is hypothesized that Thai learners show non-random use of English dependent prepositions in their English interlanguage, and that the systematicity is largely attributable to cross-linguistic influence and certain cognitive factors. To test the hypothesis, 30 L1 Thai undergraduate students of L2 English at elementary, intermediate, and advanced proficiency levels took two tests: a Thai–English translation test and a cloze test. The tests involved four types of relationship between English and Thai dependent prepositions: (1) [–prep] in English but [+prep] in Thai, (2) [+prep] in English but [–prep] in Thai, (3) [+prep1] in English but [+prep2] in Thai, and (4) [+prep] in English and [+prep] in Thai. The findings demonstrate that systematicity occurred in the learners’ English usage of prepositions of all such types, possibly due to negative transfer from the learners’ native language. Also, the L2 learners tended to exhibit such systematicity irrespective of their English proficiency level. It may be assumed that the cognitive aspect of L2 learners’ working memory is involved in processing the usage of the four types of English dependent prepositions. The results of the study are expected to shed light on the problems of L2 English interlanguage of dependent prepositions among L1 Thai learners.